Stakeholders' opinions and questions regarding the anticipated malaria vaccine in Tanzania. (December 2016) - Mtenga, Sally; Kimweri, Angela; Romore, Idda; Ali, Ali; Exavery, Amon; Sicuri, Elisa; Tanner, Marcel; Abdulla, Salim; Lusingu, John; Kafuruki, Shubi
Abstract Background Within the context of combined interventions, malaria vaccine may provide additional value in malaria prevention. Stakeholders' perspectives are thus critical for informed recommendation of the vaccine in Tanzania. This paper presents the views of stakeholders with regards to malaria vaccine in 12 Tanzanian districts. Methods Quantitative and qualitative methods were employed. A structured questionnaire was administered to 2123 mothers of under five children. Forty-six in-depth interviews and 12 focus group discussions were conducted with teachers, religious leaders, community health workers, health care professionals, and scientists. Quantitative data analysis involved frequency distributions and cross tabulations using Chi square test to determine the association between malaria vaccine acceptability and independent variables. Qualitative data were analysed thematically. Results Overall, 84.2 % of the mothers had perfect acceptance of malaria vaccine. Acceptance varied significantly according to religion, occupation, tribe and region (p < 0.001). Ninety two percent reported that they will accept the malaria vaccine despite the need to continue using insecticide-treated nets (ITNs), while 88.4 % reported that they will accept malaria vaccine even if their children get malaria less often than non-vaccinated children. Qualitative results revealed that the positive opinions towards malaria vaccine were due to a need for additional malaria prevention strategies and expectations that the vaccine will reduce visits to the health facility, deaths, malaria episodes and treatment-related expenses. Vaccine related questions included its side effects, efficacy, protective duration, composition, interaction with other medications, provision schedule, availability to the pregnant women, mode of administration (oral or injection?) and whether a child born of HIV virus or with a chronic illness will be eligible for the vaccine? Conclusion Stakeholders had high acceptance and positive opinions towards the combined use of the anticipated malaria vaccine and ITNs, and that their acceptance remains high even when the vaccine may not provide full protection, this is a crucial finding for malaria vaccine policy decisions in Tanzania. An inclusive communication strategy should be designed to address the stakeholders' questions through a process that should engage and be implemented by communities and health care professionals. Social cultural aspects associated with vaccine acceptance should be integrated in the communication strategy.